Subclinical immune reactions to viral infections may correlate with child and adolescent diagnosis of attention-deficit/hyperactivity disorder: a preliminary study from Turkey - HAKYEMEZ, İSMAİL NECATİ; Bekdas, Mervan; Tufan, Ali Evren; Hakyemez, Ismail Necati; Tas, Tekin; Altunhan, Huseyin; Demircioglu, Fatih; Kismet, Erol (My University, 2014)
Background: Attention-Deficit/Hyperactivity Disorder (ADHD) is one of the most common neuro-developmental disorders of childhood and adolescence. Studies focusing on the relationship of infectious agents and ADHD are scarce. It is also known that cerebellar injury may lead to hyperactive behavior. This study aimed to evaluate the relationship between viral agents of cerebellitis and the diagnosis of ADHD.